2022
DOI: 10.3389/fpubh.2022.853056
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aromatherapy on Anxiety and Depression in People With Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundAnxiety and depression are highly prevalent in people with cancer. Medical therapies are usually prescribed to alleviate anxiety and depression, but they are associated with a variety of adverse effects. Recently, aromatherapy showed potential as a complementary medicine to improve psychological health and wellbeing. However, its effectiveness on relieving anxiety and depression has not been established.ObjectiveThis study explored the beneficial effects of aromatherapy on psychological symptoms such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…If the results obtained from this study are compared to scientific evidence already available in the current literature, the use of Melissa Officinalis essential oil applied through a massage has a positive effect both on the agitation levels (Wilkinson et al, 2007;Li et al, 2022) and above all on the levels of the quality of life, as shown in various studies in patients affected by moderate to severe Alzheimer's. The results obtained from this experiment are, therefore, in line with the study by Ballard et al, carried out in 2002(Ballard et al, 2002Watson et al, 2019) and with the study by Burns et al, carried out in 2011(Burns et al, 2011.…”
Section: Discussionmentioning
confidence: 61%
“…If the results obtained from this study are compared to scientific evidence already available in the current literature, the use of Melissa Officinalis essential oil applied through a massage has a positive effect both on the agitation levels (Wilkinson et al, 2007;Li et al, 2022) and above all on the levels of the quality of life, as shown in various studies in patients affected by moderate to severe Alzheimer's. The results obtained from this experiment are, therefore, in line with the study by Ballard et al, carried out in 2002(Ballard et al, 2002Watson et al, 2019) and with the study by Burns et al, carried out in 2011(Burns et al, 2011.…”
Section: Discussionmentioning
confidence: 61%
“…Laughter (laughter therapy, laughter yoga) and humor interventions have been useful in improving depression, anxiety, and sleep quality 99,100 . Aromatherapy for cancer patients was useful in improving anxiety, but its effects on depression are controversial 101,102 . Lavender was useful for depression and anxiety 103 .…”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%
“… 99 , 100 Aromatherapy for cancer patients was useful in improving anxiety, but its effects on depression are controversial. 101 , 102 Lavender was useful for depression and anxiety. 103 A video game intervention was useful for improving depressive symptoms.…”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%
“…It uses pure natural essential oils taken from plants, which can have a beneficial effect on the body and mind (Brennan et al, 2022). It has been found to reduce anxiety, depression, and other negative emotions to efficiently improve physical and mental comfort (Li et al, 2022). Aromatherapy regulates mood by connecting olfaction and the limbic system to stimulate the release of endorphins and serotonin (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%